2008
DOI: 10.1007/s11460-008-0072-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of atmospheric pressure plasma polishing method in machining of silicon ultra-smooth surfaces

Abstract: The modern optics industry demands rigorous surface quality with minimum defects, which presents challenges to optics machining technologies. There are always certain defects on the final surfaces of the components formed in conventional contacting machining processes, such as micro-cracks, lattice disturbances, etc. It is especially serious for hard-brittle functional materials, such as crystals, glass and ceramics because of their special characteristics. To solve these problems, the atmospheric pressure pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Another much wider area for the use of plasma is material modification. Plasma‐polishing, for example, has proved to attain smooth surfaces for complex shapes that cannot be achieved by mechanical procedures . Likewise, plasma‐spraying can provide tailored surface coatings and structures .…”
Section: Fields Of Application For Plasma Technologiesmentioning
confidence: 99%
“…Another much wider area for the use of plasma is material modification. Plasma‐polishing, for example, has proved to attain smooth surfaces for complex shapes that cannot be achieved by mechanical procedures . Likewise, plasma‐spraying can provide tailored surface coatings and structures .…”
Section: Fields Of Application For Plasma Technologiesmentioning
confidence: 99%
“…Applying this technique, Zhang et al accomplished smoothing of silicon surfaces where a reduction from 2.39 to 1 nm (root mean squared roughness Rq) and 1.76 to 0.63 nm (Ra) was achieved [4]. A reduction in surface roughness was also reported in the case of plasma jet machining of silicon carbide (SiC) surfaces [5].…”
Section: Introductionmentioning
confidence: 99%
“…Stable plasma discharge can be observed between 100 and 800 W power. Zhang et al 65 showed the machining of silicon wafer ultra-smooth surface. The spatial gas and temperature distributions on the workpiece surface were analyzed using the finite element method.…”
Section: Magneto-rheological Finishingmentioning
confidence: 99%